FORESTRY COMPANY SATISFACTION TOWARDS ONLINE INFORMATION SYSTEM IMPLEMENTATION OF FOREST PRODUCT MANAGEMENT (SI-PUHH) - Mangatas Simanjuntak; Arief Daryanto; Teddy Rusolono (Indonesian Journal of Business and Entrepreneurship (IJBE), 2016)
This research was conducted with the aim 1) to analyze gaps that occurs between perception and expectations of the company implementation of SI-PUHH Online, 2) to analyze the level of satisfaction of the company implementation of SI-PUHH Online 3) Formulate a strategy to improve the quality of service implementation PUHH Information System Online. Analysis of the data used is the Importance Performance Analysis (IPA) and the Customer Satisfaction Index (CSI). The results showed that there are five attributes that considered important in determining customer satisfaction. These five attributes are: 1) System Online has a server that is up to date with internet bandwidth that is large so it is not easy down and can be accessed quickly; 2) response rapid administrator/operator; 3) accurate data in accordance with entrian company; 4) There is a backup server; and 5) Officer SI-Online PUHH always willing to help. The fifth attribute is an attribute that has a high level of importance, but in its implementation or performance is still unsatisfactory. Customer Satisfaction Index (CSI) on the implementation of this SIPUHH Online amounted to 72,07%, meaning that customers "satisfied" on the performance of services carried out by the Ministry of Environment and Forestry, but must maintain and improve the performance SERVQUAL PUHH Information System Online is to be able to satisfy the users company PUHH Information System Online.Keywords: SI-PUHH Online, SERVQUAL, IPA, CSI